The will of general Sowinski’s wife. Edition and analysis of archive source - Chojnacka, Maria (Requiem, 2025)
The article provides the content of Katarzyna Sowińska’s will. It introduces the people mentioned in it, and, where it was possible to determine, their connections with the testator.